THE HAHN-BANACH THEOREM FOR BOUNDED \(n\)-LINEAR FUNCTIONALS - Malčeski, Risto (Matematichki Bilten, 1999)
In [5] was introduced the concept of an \(n\)-normed space. In this paper are considered \(n\)-functionals and it s connection with bounded linear functionals defined on the factor-space on \((n-1)\)-dimensional subspace of a \(n\)-normed space and analogy of the Hahn-Banach theorem for the bounded linear \(n\)-functionals.